2018
DOI: 10.33899/rjs.2018.159344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some Biological Agents on Pathogenicity of some Root Pathogenic Fungi

Abstract: Results of pathogenicity showed that the three fungi Fusarium culmorum, Cylindrocarpon spp. and Bipolaris spp. were the faster fungi inoculated in the emergence of symptoms as pathological symptoms in both strawberry varities Hapil and Festival. Hapil was more sensitive than Festival agents on the three studied fungi. The results indicate that the addition of biological agent T. harzianum and P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…scientific research has indicated that plant decline and mortality pose a significant challenge to strawberry production, despite the fact that crown and root diseases are among the key factors that determine production, particularly during the growing season. little is known about the fungal pathogens associated with these diseases [4]. fusarium spp is IOP Publishing doi:10.1088/1755-1315/1262/3/032035 2 one of the most prevalent and economically damaging fungal pathogens affecting various plant families, including strawberries.…”
Section: Introductionmentioning
confidence: 99%
“…scientific research has indicated that plant decline and mortality pose a significant challenge to strawberry production, despite the fact that crown and root diseases are among the key factors that determine production, particularly during the growing season. little is known about the fungal pathogens associated with these diseases [4]. fusarium spp is IOP Publishing doi:10.1088/1755-1315/1262/3/032035 2 one of the most prevalent and economically damaging fungal pathogens affecting various plant families, including strawberries.…”
Section: Introductionmentioning
confidence: 99%